MICHAEL F. HENDY – BYZANTINE HISTORIAN AND NUMISMATIST: BIOGRAPHY & BIBLIOGRAPHY - Matthew Gray Marsh (Journal of Ancient History and Archaeology)
Michael F. Hendy was a noted Byzantine historian and numismatist who was active in the mid-to-late 20th century. Trained at the University of Oxford, and effectively mentored by noted historian and numismatist Philip Grierson, Hendy would publish three seminal works on Byzantine coinage, economy and fiscal administration.  This article will provide a brief biography of Professor Hendy, along with a bibliography of his published works and reviews by other scholars of his work. Byzantine Historian, Biography, Bibliography, 20th Century Historian, Numismatics, Ancient History, Byzantine Empire, Administrative History, Coinage